Statistiques de produit croisé pour l’analyse exploratoire de la dépendance spatiale - Jean-Marc Zaninetti (Unité Mixte de Recherche 8504 Géographie-cités, 2007)
Nowadays, cross-product statistics provide a complete set of procedures for exploratory spatial analysis, applied both to point patterns analysis as well as to map or image interpretation. Derived from the Mantel test in Epidemiology, these statistics developed in two main directions: correlation analysis and spatial auto regression by the generalised Mantel test on the one hand, global and local analysis of spatial dependency with correlograms and local indicators of spatial autocorrelation on the other hand.